Relationship between pulmonary function and degree of spinal deformity, location of apical vertebrae and age among adolescent idiopathic scoliosis patients - Johari, Joehaimey; Sharifudin, Mohd Ariff; Ab Rahman, Azriani; Omar, Ahmad Sabri; Abdullah, Ahmad Tajudin; Nor, Sobri; Lam, Wei Cheak; Yusof, Mohd Imran (Singapore Medical Association, 2016)
This retrospective review aimed to examine the relationship between preoperative pulmonary function and the Cobb angle, location of apical vertebrae and age in adolescent idiopathic scoliosis (AIS). To our knowledge, there have been no detailed analyses of preoperative pulmonary function in relation to these three factors in AIS. METHODS A total of 38 patients with thoracic or thoracolumbar scoliosis were included. Curvature of spinal deformity was measured using the Cobb method. Forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) were used to evaluate preoperative pulmonary function. Statistical methods were used to analyse the relationship between preoperative pulmonary function and the factors that may contribute to poor pulmonary function. The mean age of the patients was 16.68 ± 6.04 years. An inverse relationship was found between the degree of the Cobb angle and FVC as well as FEV1; however, the relationships were not statistically signi cant (p = 0.057 and p = 0.072, respectively). There was also a trend towards a signi cant negative correlation between the thoracic curve and FVC (p = 0.014). Patients with larger thoracic curves had lower pulmonary function. A one-year increase in age significantly decreased FVC by 1.092 units (p = 0.044). No signi cant relationship between age and preoperative FEV1 was found. The median FVC was significantly higher in patients with affected apical vertebrae located at levels L1–L3 than at T6–T8 or T9–T12 (p = 0.006). Lung function impairment was seen in more severe spinal deformities, proximally-located curvature and older patients.